2021
DOI: 10.1111/jfs.12891
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of chemical composition and antibacterial activity of alcoholic, hydroalcoholic extracts, and essential oil of Spinacia oleracea leaves from Iran

Abstract: This study is to investigate the antibacterial activity of the alcoholic and hydroalcoholic extracts of Spinacia oleracea leaves, on Listeria monocytogenes (ATCC 7644), Salmonella enteritidis (ATCC 13076), Escherichia coli O157:H7 (NCTC 12900) and Pseudomonas aeruginosa (ATCC 15442), and to identify bioactive functional components including essential oil by GC–MS. Microbial analyses, including disc diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) were conducted, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Issazadeh and et al showed that the alcoholic extract of the Iranian spinach variety had antimicrobial properties due to its high content of phenolic compounds, unsaturated fatty acids, amino acids, terpenes, alkaloids, etc. and hence could be used as an antibiotic 35 . Dehkharghanian also confirmed the presence of polyphenols and flavonoids in aqueous spinach extract 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Issazadeh and et al showed that the alcoholic extract of the Iranian spinach variety had antimicrobial properties due to its high content of phenolic compounds, unsaturated fatty acids, amino acids, terpenes, alkaloids, etc. and hence could be used as an antibiotic 35 . Dehkharghanian also confirmed the presence of polyphenols and flavonoids in aqueous spinach extract 36 .…”
Section: Discussionmentioning
confidence: 99%
“…These components show inhibitory effects against fungi, bacteria, and viruses. Moreover, they inhibit the cyclooxygenase pathway and resist arachidonic acid from producing prostaglandin E2 [79]. This property helps develop anti-inflammatory effects for bone therapeutic applications by reducing the inflammatory issues triggered due to implant grafting.…”
Section: In-vitro Biocompatibility Analysismentioning
confidence: 99%
“…In addition, traditional uses for spinach leaves include cooling, emollient, wholesome, antipyretic, diuretic, laxative, digestible, lungs and bowel inflammation, sore throat, joint pain, thirst, sore eye, ringworm, scabies, arrest vomiting, biliousness, flatulence, and febrile [17][18]. In the food and pharmaceutical industry, spinach extract can be utilized as a natural antibacterial and preservative [19]. However, to our knowledge, there has yet to be a systemic research report on the effect of chitosan foliar treatment on spinach production.…”
Section: Introductionmentioning
confidence: 99%